2022
DOI: 10.3389/fpls.2022.938865
|View full text |Cite
|
Sign up to set email alerts
|

Distinct rhizosphere soil responses to nitrogen in relation to microbial biomass and community composition at initial flowering stages of alfalfa cultivars

Abstract: In the long-term growth process, alfalfa rhizosphere forms specific microbiome to provide nutrition for its growth and development. However, the effects of different perennial alfalfa cultivars on changes in the rhizosphere soil characteristics and microbiome are not well understood. In this study, 12 perennial alfalfa cultivars were grown continuously for eight years. Rhizosphere samples were tested using Illumina sequencing of the 16S rRNA gene coupled with co-occurrence network analysis to explore the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…4.2 Effects of nitrogen and phosphorus rationing on inorganic phosphorus fractions in soils under alfalfa production Inorganic P is the main source of P in the soil, and changes in its content can be used as an important assessment of P uptake by plants (Urlićet al, 2023). It has been shown that N application promotes the utilization of soil P by the plant and that an appropriate ratio of N to P helps to increase soil P content (Sun et al, 2022). In our study, soil TIP content showed a decreasing trend with increasing N application (Figure 2A).…”
Section: A B D Csupporting
confidence: 52%
See 2 more Smart Citations
“…4.2 Effects of nitrogen and phosphorus rationing on inorganic phosphorus fractions in soils under alfalfa production Inorganic P is the main source of P in the soil, and changes in its content can be used as an important assessment of P uptake by plants (Urlićet al, 2023). It has been shown that N application promotes the utilization of soil P by the plant and that an appropriate ratio of N to P helps to increase soil P content (Sun et al, 2022). In our study, soil TIP content showed a decreasing trend with increasing N application (Figure 2A).…”
Section: A B D Csupporting
confidence: 52%
“…Soil pH is directly related to the utilization of nutrients by the crop, and either too acidic or alkaline can result in the inability of the crop root system to absorb nutrients ( Ringrose and Neilsen, 2005 ). Previous studies have shown that N application decreases soil pH, while P application has no significant effect on soil pH ( An et al., 2022 ). Our study indicates that both N and P application have different abilities in lowering soil pH ( Table 2 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Determining the optimal N dose is one of the most difficult challenges in plant nutrition. The key aspects in relation to N fertilizers usage are low N use efficiency (NUE) and high risk to the environment as a result of volatilization or leaching [ 13 , 14 ]. An improvement in the NUE and mitigation of the adverse effects of N on the environment, including climate change, is one of the most important prerequisites for sustainable crop management in line with the European Green Deal strategy [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of bio-fertilizers into agro-technical approaches can improve soil quality and resistance, plant growth under stresses and contribute to growth resilience of the agro-ecosystem to unfavorable effects of climate change. As recently revealed, using inoculum of the specialized microorganisms, generally referred to as arbuscular mycorrhizal fungi (AMF) or plant growth promoting rhizobacteria (PGPR), can improve the overall plant performance [ 13 , 21 , 22 , 23 ]. Thanks to AMF, water and essential nutrients from soil are more effectively exploited by host plants since AMF helps to overcome three major factors limiting nutrient uptake, i.e., its concentration (available for plant form) at the absorbing root surface, the total surface area of roots available for uptake and the distribution of roots in the soil [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%